Revisiting Buddhist Art of Living and Philosophy of Life - Wangmo, Kalsang; Kumar, Rachit (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
The rapid advancement of communication and information technology has fundamentally transformed modern society, fostering unprecedented interconnection and interdependence. This evolution resonates deeply with the Buddhist doctrine of pratītyasamutpāda (dependent origination), which asserts that all phenomena arise through mutual causality. Far from being solely a technological breakthrough, the digital age exemplifies an enduring philosophical truth. This paper critically examines the Buddhist art of living as a practical ethical framework grounded in ancient wisdom and reinterpreted in the context of globalization, digitization, and ecological uncertainty. Drawing on core Buddhist teachings, including the Four Noble Truths, the Five Aggregates (skandhas), the concept of Śūnyatā (Emptiness), and the Law of Karma, the study explores how these principles illuminate pathways toward individual well-being and collective ethics. It contends that suffering (dukkha), both personal and social, originates from distorted perceptions fueled by craving, attachment, and consumerist ideologies. When exacerbated by unchecked capitalism and technological acceleration, these afflictions undermine not only human consciousness but also the ecological and moral fabric of society. The paper highlights the dynamic interplay between individual mindfulness and collective consciousness, advocating for compassion and ethical engagement as vital forces in reshaping global values. Through the lens of Buddhist ethics, it proposes a transformative vision for humanity—one that cultivates holistic well-being, supports ecological balance, and restores spiritual integrity amidst a fragmented world. Ultimately, integrating Buddhist insights into global consciousness offers a compelling framework for sustaining harmony within the self and the broader world.